Bio-based copolyesters for head and neck repair and methods of making and using the same
Patent Information
- Application Number
- CN202610923901.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-06-25
AI Technical Summary
传统石油基高分子材料不可降解,易引发慢性炎症与异物反应;普通可降解生物基材料功能单一,缺乏天然生物活性与抗紫外能力,难以满足头颈部长期外露修复需求
[0018] (1) This invention uses natural daidzein as raw material and modifies it with hydroxyethylation to obtain a new bio-based monomer, which significantly improves its solubility and reactivity, solves the technical problem that natural daidzein is difficult to use directly in copolyester synthesis, and broadens the application scope of daidzein in the field of polymer materials.
Smart Images

Figure CN122465124B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical materials technology, specifically relating to a bio-based copolyester for head and neck repair, its preparation method, and its application. Background Technology
[0002] Developing biodegradable bio-based polymer materials has become a core direction for industry development. Gentamicin is a natural isoflavone compound widely found in legumes such as soybeans and kudzu, and is a renewable biomass resource. The isoflavone structure in genistein molecules has conjugated double bonds, which can absorb ultraviolet light and possess natural UV resistance, thus endowing materials with anti-UV aging properties. However, natural genistein suffers from poor solubility and low reactivity, making it difficult to directly copolymerize with diacids to prepare polymer materials, which greatly limits its application in the field of bio-based copolyesters.
[0003] The head and neck region has a complex anatomy, fragile tissues, and is mostly exposed. Clinical repair materials must simultaneously meet requirements such as good biocompatibility, controllable degradation, matching mechanical properties, resistance to UV aging, and promotion of tissue healing. Traditional petroleum-based polymer materials are non-degradable and easily induce chronic inflammation and foreign body reactions; ordinary biodegradable materials have limited functions, lack natural biological activity and UV resistance, and are difficult to meet the long-term exposed repair needs of the head and neck region.
[0004] Currently, existing technologies for preparing bio-based copolyesters mostly use single bio-based monomers, resulting in limited functionality and poor overall performance. Furthermore, there are no reports on the preparation of bio-based copolyesters by copolymerizing genistein with bio-based thiophene dicarboxylic acid and bio-based diols after hydroxyethylation modification. Therefore, this invention provides a bio-based polyester material suitable for head and neck repair. Summary of the Invention
[0005] The main objective of this invention is to provide a bio-based copolyester for head and neck repair, its preparation method, and its application, in order to overcome the shortcomings of the prior art.
[0006] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:
[0007] This invention provides a bio-based copolyester for head and neck repair, the bio-based copolyester having a structure as shown in formula (I):
[0008] ;
[0009] Where R is derived from bio-based diols; x and y are both independent integers from 1 to 10, and z is an integer from 10 to 200;
[0010] The bio-based copolyester is prepared by melt polycondensation of daidzein hydroxyethylated derivative, bio-based thiophene dicarboxylic acid or its ester derivative, and bio-based diol under the action of a catalyst; the daidzein hydroxyethylated derivative is 3-[4-(2-hydroxyethoxy)phenyl]-7-(2-hydroxyethoxy)-4H-chromene-4-one.
[0011] The molar ratio of repeating units derived from genistein hydroxyethylated derivatives to repeating units derived from bio-based thiophene dicarboxylic acid or its ester derivatives in the bio-based copolyester is 0.05~0.5:1.
[0012] The present invention also provides a method for preparing the aforementioned bio-based copolyester for head and neck repair, comprising: mixing a hydroxyethylated derivative of daidzein, a bio-based thiophene dicarboxylic acid or its ester derivative, a bio-based diol and a catalyst and carrying out an esterification / exchange reaction under a protective atmosphere, followed by adding a polycondensation catalyst and a stabilizer to carry out a melt polycondensation reaction to obtain the bio-based copolyester for head and neck repair.
[0013] This invention also provides a composition for preparing a bio-based copolyester for head and neck repair, comprising: a hydroxyethylated derivative of daidzein, a bio-based thiophene dicarboxylic acid or its ester derivative, and a bio-based diol;
[0014] The molar ratio of the daidzein hydroxyethylated derivative to bio-based thiophene dicarboxylic acid or its ester derivative is 0.05~0.5:1; the daidzein hydroxyethylated derivative is obtained by hydroxyethylation modification of daidzein, and the daidzein hydroxyethylated derivative is 3-[4-(2-hydroxyethoxy)phenyl]-7-(2-hydroxyethoxy)-4H-chromene-4-one.
[0015] This invention also provides the application of the aforementioned bio-based copolyester for head and neck repair in the field of head and neck repair materials, wherein the head and neck repair materials include any one of head and neck wound repair membranes, head and neck wound repair sheets, head and neck wound repair boards, oral repair materials, maxillofacial repair materials, pharyngeal mucosa repair materials, and postoperative biodegradable protective stents for head and neck.
[0016] This invention also provides a head and neck repair material, comprising: the aforementioned bio-based copolyester for head and neck repair.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0018] (1) This invention uses natural daidzein as raw material and modifies it with hydroxyethylation to obtain a new bio-based monomer, which significantly improves its solubility and reactivity, solves the technical problem that natural daidzein is difficult to use directly in copolyester synthesis, and broadens the application scope of daidzein in the field of polymer materials.
[0019] (2) The present invention uses bio-based thiophene dicarboxylic acid and bio-based diol as comonomers, and copolymerizes them with daidzein hydroxyethylated derivatives to prepare a fully bio-based, highly degradable copolyester. The material has a degradation rate of ≥60% in a natural microbial environment for 6 months, which can alleviate the environmental pollution caused by traditional petroleum-based materials from the source and meet the requirements of green and sustainable development.
[0020] (3) The bio-based copolyester prepared by this invention integrates multiple functions: it has both a high glass transition temperature and excellent UV resistance, as well as the good flexibility imparted by bio-based diols, resulting in outstanding comprehensive performance. Compared with existing bio-based copolyesters, it has richer functions and can meet the needs of multiple fields such as medical treatment, and is especially suitable for scenarios that require both UV protection and biodegradability.
[0021] (4) The preparation process of this invention is simple to operate, the reaction conditions are mild and highly controllable. It uses environmentally friendly solvents and catalysts and no toxic or harmful byproducts are generated. The raw materials are widely available and inexpensive. No complicated equipment is required. It is suitable for large-scale industrial production. By adjusting the monomer ratio and reaction parameters, the molecular weight, degradation rate, mechanical properties and UV resistance of the copolyester can be flexibly controlled, which can meet the personalized needs of different application scenarios. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 The ¹H-NMR spectrum of the hydroxyethylated daidzein derivative prepared in Example 1 of this invention is shown.
[0024] Figure 2 The ¹H-NMR spectrum of the bio-based copolyester prepared in Example 3 of this invention is shown below.
[0025] Figure 3 This is a DSC diagram of the bio-based copolyester prepared in Example 3 of the present invention. Detailed Implementation
[0026] In view of the deficiencies of the prior art, this invention, through long-term research and extensive practice, has yielded the technical solution of the present invention. The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0027] Specifically, as one aspect of the technical solution of this invention, a bio-based copolyester for head and neck repair has a structure as shown in formula (I):
[0028] ;
[0029] Where R is derived from bio-based diols; x and y are both independent integers from 1 to 10, and z is an integer from 10 to 200;
[0030] The bio-based copolyester is prepared by melt polycondensation of daidzein hydroxyethylated derivative, bio-based thiophene dicarboxylic acid or its ester derivative, and bio-based diol under the action of a catalyst; the daidzein hydroxyethylated derivative is 3-[4-(2-hydroxyethoxy)phenyl]-7-(2-hydroxyethoxy)-4H-chromene-4-one.
[0031] The molar ratio of repeating units derived from genistein hydroxyethylated derivatives to repeating units derived from bio-based thiophene dicarboxylic acid or its ester derivatives in the bio-based copolyester is 0.05~0.5:1.
[0032] In some preferred embodiments, the bio-based copolyester exhibits a degradation rate of ≥60% over 6 months at 25°C, 60%~80% humidity, and under microbial conditions, while retaining the bioactivity of daidzein.
[0033] In some preferred embodiments, the bio-based copolyester has a shielding efficiency of ≥65% in the 280~400nm ultraviolet band.
[0034] In some preferred embodiments, the bio-based copolyester retains ≥75% of its tensile strength after UV aging and shows no obvious yellowing; wherein the UV aging conditions include: 300W UV lamp, distance 50cm, irradiation for 100h.
[0035] In some preferred embodiments, the bio-based thiophene dicarboxylic acid or its ester derivatives include any one or more combinations of 2,5-thiophene dicarboxylic acid, dimethyl 2,5-thiophene dicarboxylic acid, 3,4-thiophene dicarboxylic acid, and dimethyl 3,4-thiophene dicarboxylic acid, but are not limited thereto.
[0036] In some preferred embodiments, the bio-based diols include any one or more combinations of bio-based ethylene glycol, propylene glycol, butylene glycol, pentanediol, hexanediol, and isosorbide, and all of the bio-based diols are derived from renewable biomass resources.
[0037] In some preferred embodiments, the daidzein hydroxyethylated derivative is obtained by hydroxyethylation modification of daidzein.
[0038] Another aspect of the present invention provides a method for preparing the aforementioned bio-based copolyester for head and neck repair, comprising: mixing a hydroxyethylated derivative of daidzein, a bio-based thiophene dicarboxylic acid or its ester derivative, a bio-based diol with a catalyst and carrying out an esterification / exchange reaction under a protective atmosphere, followed by adding a polycondensation catalyst and a stabilizer to carry out a melt polycondensation reaction to obtain the bio-based copolyester for head and neck repair.
[0039] In some preferred embodiments, the preparation method of the bio-based copolyester includes: weighing genistein hydroxyethylated derivative, bio-based thiophene dicarboxylic acid or its ester derivative, and bio-based diol according to the molar ratio, adding them to a reaction vessel, adding a catalyst, purging with an inert gas for protection, and heating to carry out an esterification / transesterification reaction. After the reaction is completed, adding a polycondensation catalyst and a stabilizer, then continuing to raise the temperature and gradually lowering the system pressure until the reaction system torque stabilizes, and stopping the reaction. After cooling and removal, a bio-based copolyester based on genistein hydroxyethylated derivative is obtained.
[0040] In some preferred embodiments, the preparation method specifically includes: mixing a hydroxyethylated derivative of daidzein, a bio-based thiophene dicarboxylic acid or its ester derivative, a bio-based diol, and a catalyst; then introducing a protective atmosphere and carrying out an esterification / transesterification reaction at 140-240°C for 2-8 hours; then adding a polycondensation catalyst and a stabilizer; raising the temperature to 245-255°C and reducing the pressure of the system to below 30 Pa to carry out a melt polycondensation reaction for 0.5-3 hours to obtain a bio-based copolyester for head and neck repair.
[0041] Furthermore, the temperature of the esterification / exchange reaction is 160-200℃.
[0042] Furthermore, the esterification / exchange reaction takes 3-5 hours.
[0043] Furthermore, the molar ratio of the daidzein hydroxyethylated derivative to bio-based thiophene dicarboxylic acid or its ester derivative is 0.05~0.5:1.
[0044] Furthermore, the molar ratio of the bio-based diol to the bio-based thiophene dicarboxylic acid or its ester derivative is 1.0~1.45:1.
[0045] Furthermore, the amount of catalyst used in the bio-based copolyester is 100-2000 ppm of the theoretical product mass.
[0046] Furthermore, the catalyst includes any one or more combinations of zinc acetate, antimony glycol, and dibutyltin oxide, and is not limited thereto.
[0047] Furthermore, the polycondensation catalyst includes any one or more combinations of tetrabutyl titanate, germanium oxide, and antimony trioxide, but is not limited thereto.
[0048] Furthermore, the stabilizer includes, but is not limited to, any one or more combinations of trimethyl phosphate and triphenyl phosphate.
[0049] In some preferred embodiments, the preparation method of the genistein hydroxyethylated derivative includes: dissolving the genistein monomer in an organic solvent and stirring until completely dissolved; adding an alkaline catalyst and slowly adding a hydroxyethylating agent; controlling the reaction temperature at 60-120°C and reacting at a constant temperature for 2-8 hours to obtain a reaction solution; then adjusting the pH of the reaction solution to neutral using a weak acid; filtering and washing with distilled water 3-5 times; collecting the filter residue; recrystallizing the filter residue using an ethanol-water mixed solvent; and drying at 60-80°C for 4-12 hours to obtain the genistein hydroxyethylated derivative; wherein the alkaline catalyst includes potassium carbonate; and the hydroxyethylating agent includes ethylene carbonate.
[0050] Another aspect of the present invention provides a composition for preparing a bio-based copolyester for head and neck repair, comprising: a hydroxyethylated derivative of daidzein, a bio-based thiophene dicarboxylic acid or an ester derivative thereof, and a bio-based diol;
[0051] The molar ratio of the daidzein hydroxyethylated derivative to bio-based thiophene dicarboxylic acid or its ester derivative is 0.05~0.5:1; the daidzein hydroxyethylated derivative is obtained by hydroxyethylation modification of daidzein, and the daidzein hydroxyethylated derivative is 3-[4-(2-hydroxyethoxy)phenyl]-7-(2-hydroxyethoxy)-4H-chromene-4-one.
[0052] Another aspect of the present invention provides the application of the aforementioned bio-based copolyester for head and neck repair in the field of head and neck repair materials, wherein the head and neck repair materials include any one of head and neck wound repair membranes, head and neck wound repair sheets, head and neck wound repair boards, oral repair materials, maxillofacial repair materials, pharyngeal mucosa repair materials, and postoperative biodegradable protective stents for head and neck.
[0053] Another aspect of the present invention provides a head and neck repair material, comprising: the aforementioned bio-based copolyester for head and neck repair.
[0054] The technical solution of the present invention will be further described in detail below with reference to several preferred embodiments and accompanying drawings. This embodiment is implemented on the premise of the technical solution of the invention, and provides detailed implementation methods and specific operation processes. However, the protection scope of the present invention is not limited to the following embodiments.
[0055] Unless otherwise specified, the experimental materials used in the examples below can be purchased from conventional biochemical reagent companies.
[0056] In the following examples, 1H-NMR spectra were determined using nuclear magnetic resonance spectroscopy (Bruker, 600MHz AVANCE NEO 600). Deuterated chloroform (CDCL3) was used as the solvent for the monomers. Deuterated trifluoroacetic acid (CF3COOD) was used as the solvent for the polymers.
[0057] In the following embodiments, a differential scanning calorimeter (METTLER TOLEDO DSC3+) was used to test the thermal conversion performance under N2 atmosphere, with a temperature range of 0℃-300℃, a heating / cooling rate of 10℃ / min, and a holding time of 3min.
[0058] In the following examples, an Ubbelohde viscometer was used to test the intrinsic viscosity. 0.125 g of sample, accurate to 0.1 mg, was weighed on an analytical balance and transferred to a 25 ml volumetric flask. Solvent (phenol: 1,1,2,2-tetrachloroethane = 60:40 (m / m)) was added, and the flask was capped and pretreated at 120°C for 3 hours. After the sample was completely dissolved, the outflow time was measured using an Ubbelohde viscometer (0.88 mm inner diameter) in a 25°C constant temperature water bath. The intrinsic viscosity of the polyester sample could then be calculated using a formula.
[0059] In the following examples, tensile strength was tested using a 1KN universal testing machine (Zwick / Roell Z1.0), and the samples were prepared in a dumbbell shape.
[0060] In the following examples, a fluorescent ultraviolet aging test chamber (Q-LAB QUV) was used for ultraviolet aging experiments. Experimental conditions: 300W ultraviolet lamp, distance 50cm, irradiation for 100h.
[0061] In the following examples, a constant temperature and humidity chamber (BPS-50CL) was used for degradation experiments. Experimental conditions: 25℃, humidity 60%~80%, under microbial conditions.
[0062] Example 1
[0063] The synthetic route for preparing the hydroxyethylated derivative of daidzein 3-[4-(2-hydroxyethoxy)phenyl]-7-(2-hydroxyethoxy)-4H-chromen-4-one is as follows:
[0064]
[0065] 100g of daidzein monomer was dissolved in 200ml of organic solvent N,N-dimethylacetamide (DMAC). After stirring until completely dissolved, potassium carbonate (K2CO3) was added as an alkaline catalyst, and ethylene carbonate (EC) was slowly added dropwise. The reaction temperature was controlled at 100℃, and the reaction was carried out at a constant temperature for 5 hours to obtain the reaction solution. The pH was adjusted to neutral with a weak acid, filtered, and washed three times with distilled water. The residue was collected by vacuum filtration. The residue was recrystallized with anhydrous ethanol and dried in a vacuum oven at 60℃ for 8 hours to obtain a high-purity hydroxyethylated daidzein derivative.
[0066] The NMR spectrum of the target product, daidzein hydroxyethylated derivative, is shown below. Figure 1 The results are as follows: the absorption peak at chemical shift δ=2.5ppm corresponds to the proton peak of the deuterated reagent DMSO, and the reference signal peak of the internal standard tetramethylsilane (TMS) is located at 0ppm.
[0067] In the 1H NMR spectrum, the signals at chemical shifts of 8.40 ppm, 7.51 ppm, 7.17 ppm, and 6.96 ppm correspond to aromatic protons on the benzo[a]oxy-containing heterocycle in the genistein skeleton; the signal at 8.04 ppm corresponds to a proton on the benzo[a]oxy-containing heterocycle; and the signal at 7.10 ppm corresponds to an aromatic proton on the para-substituted benzene ring in the genistein. The signals at 4.15 ppm, 4.02 ppm, 3.77 ppm, and 3.34 ppm originate from the methylene (-CH2-) protons extended after hydroxyethylation of the genistein. The peaks at 4.97 and 4.90 ppm correspond to the hydroxyl (-OH) protons at the hydroxyethyl terminus. The spectrum indicates that the genistein was successfully hydroxyethylated while retaining its isoflavone characteristic structure. The target product is 3-[4-(2-hydroxyethoxy)phenyl]-7-(2-hydroxyethoxy)-4H-chromene-4-one.
[0068] Example 2
[0069] Dimethyl 2,5-thiophene dicarboxylate, a hydroxyethylated derivative of genistein (prepared in Example 1), and ethylene glycol were added to a three-necked flask in a molar ratio of 1:0.05:1.45. Then, 500 ppm of zinc acetate catalyst was added, and the mixture was protected with high-purity nitrogen. The temperature was raised to 160°C for transesterification. After the reaction was complete, 500 ppm of tetrabutyl titanate condensation catalyst and 1000 ppm of trimethyl phosphate stabilizer were added. The temperature was then raised to 245°C, and the system pressure was gradually reduced to 10 Pa. Finally, the reaction was stopped when the torque of the reaction system stabilized (the stirring torque of the reactor stabilized), yielding a bio-based copolyester with the following structure:
[0070] .
[0071] Example 3
[0072] 2,5-Thiophene dicarboxylic acid, a hydroxyethylated derivative of daidzein (prepared in Example 1), and ethylene glycol were added to a three-necked flask in a molar ratio of 1:0.3:1.2. Then, 300 ppm of antimony glycolate catalyst was added, and the mixture was protected with high-purity nitrogen. The temperature was raised to 170°C for esterification. After the reaction was complete, 500 ppm of germanium oxide polycondensation catalyst and 800 ppm of triphenyl phosphate stabilizer were added. The temperature was then raised to 250°C, and the system pressure was gradually reduced to 10 Pa. Finally, the reaction was stopped when the system torque stabilized, yielding a bio-based copolyester.
[0073] The 1H NMR spectrum of the prepared bio-based copolyester is shown in the figure. Figure 2 In the ¹H NMR spectrum of the target bio-based copolyester (solvent: deuterated trifluoroacetic acid, TFA-d), the characteristic signal peaks were assigned as follows: the signals at chemical shifts of 8.9–8.6 ppm and 7.96–7.8 ppm correspond to the aromatic protons on the hydroxyethyl daidzein core and the thiophene ring, respectively; the signal at chemical shifts of 4.88–4.3 ppm corresponds to the methylene (-CH2-) protons in the ethylene glycol unit and the side chain of the hydroxyethyl daidzein in the polymer chain. The spectrum indicates that thiophene dicarboxylic acid, ethylene glycol, and hydroxyethyl daidzein successfully underwent a polymerization reaction to form the target polyester structure.
[0074] The DSC pattern of the prepared bio-based copolyester is shown in the figure. Figure 3 As shown.
[0075] Example 4
[0076] 3,4-Thiophene dicarboxylic acid, a hydroxyethylated derivative of daidzein (prepared in Example 1), and ethylene glycol were added to a three-necked flask in a molar ratio of 1:0.5:1.0. Then, 600 ppm of dibutyltin oxide catalyst was added, and the mixture was protected with high-purity nitrogen. The temperature was raised to 180°C for esterification. After the reaction was complete, 300 ppm of antimony trioxide condensation catalyst and 900 ppm of triphenyl phosphate stabilizer were added. The temperature was then raised to 255°C, and the system pressure was gradually reduced to 10 Pa. Finally, the reaction was stopped when the system torque stabilized, yielding a bio-based copolyester.
[0077] Example 5
[0078] In Example 3, propylene glycol was replaced with butanediol, and the subsequent process was the same as in Example 3. The structure is as follows:
[0079] .
[0080] Example 6
[0081] In Example 3, ethylene glycol was replaced with butanediol, and the subsequent process was the same as in Example 3. The structure is as follows:
[0082] .
[0083] Example 7
[0084] In Example 3, ethylene glycol was replaced with pentanediol, and the subsequent process was the same as in Example 3. The structure is as follows:
[0085] .
[0086] Example 8
[0087] In Example 3, ethylene glycol was replaced with hexanediol, and the subsequent process was the same as in Example 3. The structure is as follows:
[0088] .
[0089] Example 9
[0090] 2,5-Thiophene dicarboxylic acid, genistein hydroxyethylated derivative (prepared in Example 1), isosorbide, and ethylene glycol were added to a three-necked flask in a molar ratio of 1:0.3:0.2:1.0. The subsequent process was the same as in Example 3. The structure is as follows:
[0091] .
[0092] Comparative Example 1
[0093] The 2,5-thiophene dicarboxylic acid in Example 3 was replaced with petroleum-based terephthalic acid, and the subsequent process was the same as in Example 3.
[0094] Comparative Example 2
[0095] All the hydroxyethylated derivatives of daidzein in Example 3 were replaced with ethylene glycol, and the subsequent process was the same as in Example 3.
[0096] Comparative Example 3
[0097] In Example 3, all hydroxyethylated genistein derivatives were replaced with unmodified genistein, and the subsequent process was the same as in Example 3. It was found that genistein was difficult to dissolve in the reaction system and could not undergo effective transesterification and polycondensation reactions, ultimately failing to obtain the target bio-based copolyester. This indicates that hydroxyethylation modification is crucial for genistein to participate in copolyester preparation.
[0098] Comparative Example 4
[0099] The method is the same as in Example 3, except that the molar ratio of the hydroxyethylated derivative of daidzein to bio-based thiophene dicarboxylic acid or its ester derivative is 0.01:1.
[0100] Comparative Example 5
[0101] The method is the same as in Example 3, except that the molar ratio of the hydroxyethylated daidzein derivative to bio-based thiophene dicarboxylic acid or its ester derivative is 1:1. During the polymerization process, it was found that after the reaction system reached the polycondensation stage, the melt viscosity increased sharply in a short time, and rapid cross-linking and gelation occurred, making it impossible to obtain a thermoplastic linear copolyester product.
[0102] The copolyesters prepared in Examples 2-9 and Comparative Examples 1-5 were tested, and the results are shown in Table 1.
[0103] Table 1
[0104] As can be seen from the test data in Table 1, the copolyester prepared in Example 3 exhibits outstanding comprehensive performance, with excellent degradation, UV resistance, and aging resistance. In Comparative Example 1, the degradation and UV resistance of the material decreased significantly after using a petroleum-based monomer and Comparative Example 2, the material could not be synthesized using unmodified genistein. In Comparative Example 4, the amount of genistein added was too low, resulting in insufficient functionality. In Comparative Example 5, the addition of too much genistein caused polymerization and gelation. This confirms that the hydroxyethyl modification of genistein and the ratio range of 0.05~0.5:1 are the key to achieving excellent comprehensive performance of the material.
[0105] Example 3 is the preferred formulation of the present invention, with an intrinsic viscosity of 0.79 dL / g and a glass transition temperature of 84℃; a microbial degradation rate of 67% and an ultraviolet shielding rate of 86% after 6 months; a tensile strength retention rate of 80% after ultraviolet aging; and no obvious yellowing. It combines excellent degradation, ultraviolet resistance, heat resistance and mechanical stability, and has the best comprehensive performance. It can be used as a medical material for head and neck repair.
[0106] In addition, this case also referred to the foregoing embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and all of them obtained relatively ideal results.
[0107] It should be understood that the technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made to the technical solutions of the present invention without departing from the spirit and scope of the claims are within the scope of protection of the present invention.
Claims
1. A bio-based copolyester for head and neck repair, characterized in that, The bio-based copolyester has a structure as shown in formula (I): ; Where R is derived from bio-based diols; x and y are both independent integers from 1 to 10, and z is an integer from 10 to 200; The bio-based copolyester is prepared by melt polycondensation of a hydroxyethylated derivative of daidzein, bio-based thiophene dicarboxylic acid or its ester derivative, and a bio-based diol containing isosorbide under the action of a catalyst; wherein, the polycondensation catalyst added in the melt polycondensation reaction is tetrabutyl titanate, and the stabilizer is trimethyl phosphate; the hydroxyethylated derivative of daidzein is 3-[4-(2-hydroxyethoxy)phenyl]-7-(2-hydroxyethoxy)-4H-chromene-4-one; the bio-based thiophene dicarboxylic acid or its ester derivative includes any one or more combinations of 2,5-thiophene dicarboxylic acid, dimethyl 2,5-thiophene dicarboxylic acid, 3,4-thiophene dicarboxylic acid, and dimethyl 3,4-thiophene dicarboxylic acid. The molar ratio of repeating units derived from genistein hydroxyethylated derivatives to repeating units derived from bio-based thiophene dicarboxylic acid or its ester derivatives in the bio-based copolyester is 0.05~0.5:
1. The bio-based copolyester exhibits a degradation rate of ≥60% over 6 months under microbial conditions at 25°C and 60%~80% humidity; and its shielding efficiency in the 280~400nm ultraviolet band is ≥65%. The bio-based copolyester retains ≥75% of its tensile strength after UV aging. The UV aging conditions include: 300W UV lamp, 50cm distance, and 100h irradiation.
2. The bio-based copolyester for head and neck repair according to claim 1, characterized in that: The bio-based diols also include any one or more combinations of bio-based ethylene glycol, propylene glycol, butanediol, pentanediol, and hexanediol, all of which are derived from renewable biomass resources.
3. The method for preparing the bio-based copolyester for head and neck repair as described in any one of claims 1-2, characterized in that, include: A bio-based copolyester for head and neck repair was prepared by mixing a hydroxyethylated derivative of daidzein, a bio-based thiophene dicarboxylic acid or its ester derivative, a bio-based diol containing isosorbide, and a catalyst under a protective atmosphere and carrying out an esterification / transesterification reaction. Then, tetrabutyl titanate as a polycondensation catalyst and trimethyl phosphate as a stabilizer were added to carry out a melt polycondensation reaction.
4. The preparation method according to claim 3, characterized in that, Specifically, it includes: A hydroxyethylated derivative of daidzein, bio-based thiophene dicarboxylic acid or its ester derivative, a bio-based diol, and a catalyst are mixed, and then an esterification / exchange reaction is carried out at 140-240°C for 2-8 hours under a protective atmosphere. Then, tetrabutyl titanate as a polycondensation catalyst and trimethyl phosphate as a stabilizer are added, and the temperature is raised to 245-255°C and the pressure of the system is reduced to below 30 Pa to carry out a melt polycondensation reaction for 0.5-3 hours to obtain a bio-based copolyester for head and neck repair.
5. The preparation method according to claim 4, characterized in that: The esterification / exchange reaction is carried out at a temperature of 160~200℃.
6. The preparation method according to claim 4, characterized in that: The esterification / exchange reaction takes 3-5 hours.
7. The preparation method according to claim 4, characterized in that: The molar ratio of the hydroxyethylated derivative of daidzein to bio-based thiophene dicarboxylic acid or its ester derivative is 0.05~0.5:
1.
8. The preparation method according to claim 4, characterized in that: The molar ratio of the bio-based diol to the bio-based thiophene dicarboxylic acid or its ester derivative is 1.0~1.45:
1.
9. The preparation method according to claim 4, characterized in that: The catalyst includes any one or a combination of zinc acetate, antimony glycol, and dibutyltin oxide.
10. The preparation method according to claim 3, characterized in that, The preparation method of the genistein hydroxyethylated derivative includes: dissolving the genistein monomer in an organic solvent and stirring until completely dissolved; adding an alkaline catalyst and slowly adding a hydroxyethylating agent; controlling the reaction temperature at 60-120℃ and reacting at a constant temperature for 2-8 hours to obtain a reaction solution; then adjusting the pH of the reaction solution to neutral using a weak acid; filtering and washing with distilled water 3-5 times; collecting the filter residue; recrystallizing the filter residue using an ethanol-water mixed solvent; and drying at 60-80℃ for 4-12 hours to obtain the genistein hydroxyethylated derivative; wherein the alkaline catalyst includes potassium carbonate; and the hydroxyethylating agent includes ethylene carbonate.
11. The use of the bio-based copolyester for head and neck repair according to any one of claims 1-2 in the preparation of head and neck repair materials, wherein, The head and neck repair materials include any one of the following: head and neck wound repair membrane, head and neck wound repair sheet, head and neck wound repair board, pharyngeal mucosa repair material, and postoperative biodegradable protective stent for head and neck.
12. A head and neck repair material, characterized in that, include: The bio-based copolyester for head and neck repair according to any one of claims 1-2.
Citation Information
Patent Citations
Degradable copolyester based on thiophenedicarboxylic acid and ethylene glycol as well as preparation method and product thereof
CN115260476A
Biodegradable shape memory material as well as preparation method and application thereof
CN119978287A